Determinants of the Engagement of Virtual Runs' Participants in the Co-creation of Customer Value during the Pandemic - Zygmunt Waśkowski; Anna Jasiulewicz (Kazimierz Wielki University, 2022)
The study focuses on the research question of the determinants and motivating factors which stimulate  consumers to engage in the co-creation of customer value, even though the product they are offered is merely a substitute for the one they are used to. The research focuses on the virtual runs and its subject are the runners participating in the Białystok Virtual Half-Marathon. There are two equivalent objectives of the study: (a) the identification and the assessment of the determinants of the runners' engagement, and (b) the segmentation of the virtual run participants on the basis of the diagnosed determinants of their involvement. The article is based on the results of the survey conducted in 2020 on a sample of 419 runners, by means of the CAWI method. The respondents were asked to assess 17 factors related to the customer engagement in the co-creation of value, with reference to the virtual run in which they participated. The Białystok Virtual Half-Marathon, the second biggest virtual run organised in 2020 in Poland, was used as a point of reference for this survey. This run was an alternative proposal prepared by the organiser in response to the Covid-19 pandemic and the ban on the organisation of real runs in the whole country. The research findings allowed for expanding the theoretical knowledge of the concept of the  customer value co-creation and the consumers' engagement in this process. The research resulted in distinguishing four meta-factors determining the runners' engagement and  establishing the strength of their influence on the customer value co-creation. The research also revealed the runners' motivation for participating in the virtual run. The runners' involvement was determined by the hedonistic and social factors, though the structure and the strength of their impact varied in relation to the respondents' demographics. All in all, four segments of runners were distinguished.